Prehospital end-tidal carbon dioxide predicts hemorrhagic shock upon emergency department arrival. Issue 3 (9th September 2021) - Bulger, Natalie; Harrington, Brenna; Krieger, Josh; Latimer, Andrew; Arbabi, Saman; Counts, Catherine R.; Sayre, Michael; Maynard, Charles; Bulger, Eileen M.
Abstract : BACKGROUND: In addition to reflecting gas exchange within the lungs, end-tidal carbon dioxide (ETCO2 ) also reflects cardiac output based on CO2 delivery to the pulmonary parenchyma. We hypothesized that low prehospital ETCO2 values would be predictive of hemorrhagic shock in intubated trauma patients. METHODS: A retrospective observational study of adult trauma patients intubated in the prehospital setting and transported to a single Level I trauma center from 2016 to 2019. Continuous prehospital ETCO2 data were linked with patient care registries. We developed a novel analytic approach that allows for reflection of prehospital ETCO2 over the entire prehospital course of care. The primary outcome was hemorrhagic shock on emergency department (ED) presentation, defined as either initial ED systolic blood pressure of 90 mm Hg or less or initial Shock Index (SI) > 0.9, and transfusion of at least one unit of blood product during their ED stay. Prehospital ETCO2 less than 25 mm Hg was evaluated for predictive value of hemorrhagic shock. RESULTS: Three hundred and seven patients (82% men, 34% penetrating injury, 42% in hemorrhagic shock on ED arrival, 27% mortality) were included in the study. Patients in hemorrhagic shock had lower median ETCO2 values (26.5 mm Hg vs. 32.5 mm Hg; p < 0.001) than those not in hemorrhagic shock. Patients with prehospital ETCO2 less than 25 mm Hg were 3.0 times (adjusted odds ratio = 3.0; 95% confidence interval, 1.1–7.9) more likely to be in hemorrhagic shock upon ED arrival than patients with ETCO2 ≥ 25 mm Hg. CONCLUSION: Intubated patients with hemorrhagic shock upon ED arrival had significantly lower prehospital ETCO2 values. Incorporating ETCO2 assessment into prehospital care for trauma patients could support decisions regarding prehospital blood transfusion, and triage to higher-level trauma centers, and trauma team activation. LEVEL OF EVIDENCE: Prognostic, level III.